Faktor-Faktor Yang Mempengaruhi Keputusan Investor Dalam Berinvestasi Di Pasar Modal Syariah - Nisa Kumalasari (FAI UMY, 2017)
Faktor-Faktor Yang Mempengaruhi Keputusan Investor Dalam Berinvestasi Di Pasar Modal Syariah